2004
DOI: 10.1108/09576050410510953
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of using an enterprise system to teach process‐centered concepts in business education

Abstract: This study investigates whether or not student's performance, self-efficacy, and satisfaction are enhanced by the use of an enterprise system as a support tool for learning business process and enterprise systems concepts. The study compares three instructional delivery methods. A traditional instruction method (lecture format plus reading/exercises) serves as the control. The second and third instructional methods are computer-based methods. In the second method, students receive traditional lecture format wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 50 publications
0
11
0
2
Order By: Relevance
“…Overall, prior research on ERPs revealed some important results, opening the path for new empirical investigations on ERP systems in a university environment, especially using ERP systems in the classroom for learning and teaching purposes (Yvonne Lederer et al, 2004) such as the usefulness of using ERP systems for enhancing learning by providing ways to transform the classroom into a real business environment (Noguera and Watson, 2004).…”
Section: Erp Systems In Higher Educationmentioning
confidence: 99%
“…Overall, prior research on ERPs revealed some important results, opening the path for new empirical investigations on ERP systems in a university environment, especially using ERP systems in the classroom for learning and teaching purposes (Yvonne Lederer et al, 2004) such as the usefulness of using ERP systems for enhancing learning by providing ways to transform the classroom into a real business environment (Noguera and Watson, 2004).…”
Section: Erp Systems In Higher Educationmentioning
confidence: 99%
“…Students receiving training in enterprise systems scored higher in tests measuring knowledge of human resources business practices but results were not statistically significant. Noguera (2000) examined student performance and self‐efficacy with different ERP instructional methods. His study found no differences in process understanding among students reviewing BPs through a Web tutorial as compared with actual experience with enterprise software.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These discussions clearly point out that ERP systems are or should be an important component of university curricula in information system-related subjects and courses. However, this is not a trivial task, as Noguera and Watson [19] discuss. Because there is no standardized approach, the choice of systems and their number, as well as the structure and number of ERP courses, differ from university to university [8].…”
Section: Introductionmentioning
confidence: 99%